Functional relatedness in the Inv/Mxi‐Spa type III secretion system family. Issue 6 (30th January 2017) - Klein, Jessica A.; Dave, Biren M.; Raphenya, Amogelang R.; McArthur, Andrew G.; Knodler, Leigh A.
Summary: Type III Secretion Systems (T3SSs) are structurally conserved nanomachines that span the inner and outer bacterial membranes, and via a protruding needle complex contact host cell membranes and deliver type III effector proteins. T3SS are phylogenetically divided into several families based on structural basal body components. Here we have studied the evolutionary and functional conservation of four T3SS proteins from the Inv/Mxi‐Spa family: a cytosolic chaperone, two hydrophobic translocators that form a plasma membrane‐integral pore, and the hydrophilic 'tip complex' translocator that connects the T3SS needle to the translocon pore. Salmonella enterica serovar Typhimurium ( S . Typhimurium), a common cause of food‐borne gastroenteritis, possesses two T3SSs, one belonging to the Inv/Mxi‐Spa family. We used invasion‐deficient S . Typhimurium mutants as surrogates for expression of translocator orthologs identified from an extensive phylogenetic analysis, and type III effector translocation and host cell invasion as a readout for complementation efficiency, and identified several Inv/Mxi‐Spa orthologs that can functionally substitute for the S . Typhimurium chaperone and translocator proteins. Functional complementation correlates with amino acid sequence identity between orthologs, but varies considerably between the four proteins. This is the first in‐depth survey of the functional interchangeability of Inv/Mxi‐Spa T3SS proteins acting directly at the host‐pathogen interface. Abstract : Type III Secretion Systems (T3SSs) are phylogenetically grouped based on highly‐conserved structural proteins. Here we have investigated the evolutionary and functional relationships of translocator proteins within the Inv/Mxi‐Spa T3SS family, which directly interface with host cells and are potentially under different selective pressures than intrabacterial T3SS structural proteins. Using Salmonella as a surrogate for ortholog expression, we show that the T3SS translocators are much less permissive to functional substitution than their cognate chaperone.